Composite material, preparation method thereof and wastewater purification method
By preparing composite materials with crosslinked polymer support and bonded sulfamic acid, the problem of insufficient adsorption and regeneration performance of existing adsorbents in COD removal is solved, and efficient adsorption and reversible regeneration of organic pollutants in water bodies is achieved.
Patent Information
- Application Number
- CN202411962837.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-07
AI Technical Summary
The existing adsorbents have problems with poor adsorption performance or cannot be reused in COD removal, and it is difficult to effectively reduce the chemical oxygen demand value of water.
By mixing monomers, initiators, crosslinking agents and pore-making agents for polymerization, a crosslinking polymer carrier is prepared and replaced with sulfamic acid to form a composite material with excellent adsorption properties and regeneration properties.
It realizes efficient adsorption and reversible regeneration functions of organic pollutants such as phenol, para-hydroxybenzoic acid and oxylic acid in water, and improves the water purification effect.
Smart Images

Figure CN119565578A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adsorption materials, and in particular to a composite material and a preparation method thereof, and a wastewater purification method. Background Art
[0002] Chemical Oxygen Demand (COD) is an important indicator to measure the degree of organic pollution in water bodies. It reflects the amount of oxygen consumed by oxidizable organic matter and reducible inorganic matter in water bodies under certain conditions. High COD values usually indicate that the water body is seriously polluted and needs effective treatment to restore its ecological balance and use value.
[0003] As an efficient, simple and relatively low-cost method, adsorption technology has been widely used and studied in the field of COD removal. In COD removal, adsorbents can capture organic matter such as phenol, p-hydroxybenzoic acid and oxalic acid in water by physical adsorption or chemical adsorption, thereby reducing the COD value of the water body. Commonly used adsorbents include: activated carbon, natural modified materials, biomass materials, and nanomaterials. However, the adsorbents reported so far have the disadvantages of poor adsorption performance or cannot be reused. Summary of the invention
[0004] Based on this, the present application provides a composite material and a preparation method thereof, and a wastewater purification method. The composite material prepared by the preparation method provided in the present application can be used as a water body adsorbent, which has both excellent adsorption performance and regeneration performance.
[0005] In a first aspect of the present application, a method for preparing a composite material is provided, comprising the following steps:
[0006] Mixing monomers, initiators, crosslinking agents and pore-forming agents, and performing polymerization reaction to prepare a crosslinked polymer carrier;
[0007] The cross-linked polymer carrier and aminosulfonic acid are mixed in a solvent, and a substitution reaction is performed to bond the aminosulfonic acid to the cross-linked polymer carrier to prepare the composite material;
[0008] Wherein, the monomer includes one or more compounds having structural characteristics shown in formula (I) to formula (II):
[0009] , ;
[0010] R 11 C 2 ~C 6 Alkynyl, substituted or unsubstituted C 2 ~C 6 Alkenyl; replace the C2 ~C 6 Substituents for alkenyl groups include C 1 ~C 3 Alkyl and C 1 ~C 3 One or more of alkoxy groups; R 12 is a halogen; m1 and m2 are positive integers, and the sum of m1 and m2 is ≤4;
[0011] R 21 , R 22 and R 23 are each independently H or halogen, and R 21 , R 22 and R 23 At least one of them is a halogen; n1 and n4 are each independently an integer from 1 to 5, n2 is 1 or 2, and n3 is an integer from 1 to 10.
[0012] In one embodiment, in formula (I), R 11 -CH=CH 2 、-CH 2 CH=CH 2 、-CH 2 CH 2 CH 2 CH 2 CH=CH 2 、-C≡CH、-CH 2 C≡CH, , or .
[0013] In one embodiment, in formula (II), R 21 , R 22 and R 23 Each is independently H, F or Cl.
[0014] In one embodiment, the monomer comprises , , and One or more of .
[0015] In one embodiment, the cross-linked polymer carrier and aminosulfonic acid are mixed in a solvent, and a substitution reaction is performed to bond the aminosulfonic acid to the cross-linked polymer carrier. The steps of preparing the composite material include:
[0016] The cross-linked polymer carrier is swollen in a solvent, and the aminosulfonic acid is added and mixed to carry out a substitution reaction so that the aminosulfonic acid is bonded to the cross-linked polymer carrier to prepare the composite material.
[0017] In one embodiment, the solvent includes one or more of N,N-dimethylformamide, ethanol, 1,4-dioxane and toluene.
[0018] In one embodiment, the mass ratio of the cross-linked polymer carrier to the solvent is 1:(1-5).
[0019] In one embodiment, the mass ratio of the cross-linked polymer carrier to the aminosulfonic acid is 1:(0.1-0.6).
[0020] In one embodiment, the swelling process parameters include: swelling temperature is room temperature, and swelling time is 2h~4h.
[0021] In one embodiment, the process parameters of the substitution reaction include: reaction temperature of 40°C to 70°C, and reaction time of 4h to 12h.
[0022] In one embodiment, the steps of mixing monomers, initiators, crosslinking agents and pore-forming agents to prepare a crosslinked polymer carrier by polymerization reaction include:
[0023] Mixing the monomer, the cross-linking agent, the initiator and the pore-forming agent to prepare an oil phase solution;
[0024] Mixing a dispersant and a salting-out agent in a water solvent to prepare an aqueous phase solution;
[0025] The oil phase solution and the water phase solution are mixed and subjected to polymerization reaction to prepare the cross-linked polymer carrier.
[0026] In one embodiment, the mass ratio of the monomer to the initiator is 1:(0.005~0.01).
[0027] In one embodiment, the mass ratio of the monomer to the cross-linking agent is 1:(0.03-0.1).
[0028] In one embodiment, the mass ratio of the monomer to the pore-forming agent is 1:(0.3-5).
[0029] In one embodiment, the initiator includes one or more of benzoyl peroxide, azobisisobutyronitrile, cumene hydroperoxide and tert-butyl hydroperoxide.
[0030] In one embodiment, the crosslinking agent includes one or more of divinylbenzene, ethylene glycol dimethacrylate, allyl methacrylate, allyl itaconate and allyl isocyanurate.
[0031] In one embodiment, the pore-forming agent includes one or more of cyclohexane, ethylene dichloride, benzene, toluene and xylene.
[0032] In one embodiment, the mass ratio of the dispersant to the aqueous solvent is 1:(80-200).
[0033] In one of the embodiments, the mass ratio of the dispersant to the salting-out agent is 1:(30~60).
[0034] In one embodiment, the dispersing agent includes one or more of polyethylene glycol and gelatin.
[0035] In one embodiment, the salting-out agent includes one or more of magnesium sulfate, sodium carbonate, sodium chloride, calcium chloride and ammonium chloride.
[0036] In one embodiment, the mass ratio of the oil phase solution to the water phase solution is 1:(1-8).
[0037] In one embodiment, the polymerization reaction includes a first polymerization reaction and a second polymerization reaction performed sequentially;
[0038] The process parameters of the first polymerization reaction include: polymerization temperature of 60°C to 80°C, polymerization time of 2h to 5h;
[0039] The process parameters of the second polymerization reaction include: polymerization temperature of 95° C. to 120° C., and polymerization time of 10 h to 18 h.
[0040] In a second aspect of the present application, a composite material is provided, which is prepared by the preparation method described in any one of the embodiments of the first aspect of the present application; the composite material comprises: a cross-linked polymer carrier and aminosulfonic acid bonded to the cross-linked polymer carrier; wherein the cross-linked polymer carrier is obtained by polymerization reaction of the monomer, the initiator, the cross-linking agent and the pore-forming agent;
[0041] The composite material has one or more of the following characteristics:
[0042] (1) The particle size of the composite material is 0.3 mm to 1.2 mm;
[0043] (2) The particle strength of the composite material is greater than 3N.
[0044] The third aspect of the present application provides a wastewater purification method, comprising the following steps: using the composite material described in the second aspect of the present application to perform adsorption treatment on a water body.
[0045] In one embodiment, the wastewater comprises one or more of phenol, p-hydroxybenzoic acid and oxalic acid.
[0046] In one embodiment, the process parameters of the adsorption treatment include: the flow rate of the wastewater is 1BV / h~3BV / h.
[0047] The preparation method of the composite material provided in this application has at least the following beneficial effects:
[0048] In the preparation method provided in the present application, a cross-linked polymer carrier is first prepared by using a monomer, an initiator, a cross-linking agent and a pore-forming agent. The cross-linked polymer carrier obtained at this time has a high specific surface area and can provide a large number of adsorption active sites, so that water organic pollutants such as phenol, p-hydroxybenzoic acid and oxalic acid can be more easily diffused into the material and adsorbed. In addition, the cross-linked network structure formed by the polymerization reaction of the cross-linked polymer carrier can give the carrier good mechanical stability and chemical stability, thereby maintaining the stability and durability of its adsorption performance.
[0049] Monomers containing pyridazine structures can produce π-π interactions with organic pollutants in water bodies such as phenol, p-hydroxybenzoic acid and oxalic acid, and the nitrogen atom in the pyridazine structure has a certain electronegativity, which can form hydrogen bonds or other interactions with functional groups such as hydroxyl and carboxyl groups in organic molecules to further improve the adsorption performance. In addition, monomers containing halogen atoms can provide sites for the bonding of cross-linked polymer carriers and aminosulfonic acid to form sulfonic acid groups on the surface of the cross-linked polymer carrier. In the water purification process, the sulfonic acid group can interact with the acidic or basic functional groups in organic molecules such as phenol, p-hydroxybenzoic acid and oxalic acid through electrostatic attraction, thereby further enhancing adsorption.
[0050] Furthermore, the adsorption between the composite material prepared by the preparation method provided in the present application and the organic pollutants is reversible, and the stable structure of the cross-linked polymer is not easily destroyed by the desorption operation, so it can have a good desorption and regeneration function by changing the external conditions.
[0051] In addition, the preparation method provided in the present application has a simple process, a high yield, and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is the FTIR spectrum of the composite material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0053] The composite material and its preparation method and wastewater purification method of the present application are further described in detail below in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0054] In this application, "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0055] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. Unless otherwise specified or there is a contradiction, the terms or phrases used herein have the following meanings:
[0057] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0058] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0059] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0060] In the present application, references to “combinations thereof”, “any combination thereof”, “any combination thereof”, etc. include all suitable combinations of any two or more of the listed items.
[0061] In this application, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc. shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.
[0062] In the present application, the terms “preferred”, “better”, “more preferred” and “suitable” are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute limitations on the scope of protection of the present application.
[0063] In the present application, the terms “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0064] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0065] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.
[0066] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0067] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.
[0068] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.
[0069] In the present application, "alkenyl" refers to a group containing at least one unsaturated site, i.e., a carbon-carbon sp 2 A hydrocarbon containing a positive, secondary, tertiary, or cyclic carbon atom with a double bond. Phrases containing this term, such as "C 2 ~C 6 "Alkenyl" refers to an alkenyl group containing 2 to 6 carbon atoms, each occurrence of which can be independently C 2 Alkenyl, C 3 Alkenyl, C 4 Alkenyl, C 5 Alkenyl or C 6 Suitable examples include, but are not limited to, vinyl (-CH=CH 2 ), allyl (-CH 2 CH=CH 2 ), cyclopentenyl (-C 5 H 7 ) and 5-hexenyl (-CH 2 CH 2 CH 2 CH 2 CH=CH 2 ).
[0070] In the present application, "alkynyl" refers to a hydrocarbon containing a positive carbon atom, a secondary carbon atom, a tertiary carbon atom or a ring carbon atom having at least one unsaturated site, i.e., a carbon-carbon sp triple bond. Phrases containing this term, such as "C 2 ~C 6 "Alkynyl" refers to an alkynyl group containing 2 to 6 carbon atoms, each occurrence of which can be independently C 2 Alkynyl, C 3 Alkynyl, C 4 Alkynyl, C 5 Alkynyl or C 6 Suitable examples include, but are not limited to, ethynyl (-C≡CH) and propargyl (-CH 2 C≡CH).
[0071] In this application, "alkyl" refers to a saturated hydrocarbon group containing primary (normal) carbon atoms, secondary carbon atoms, tertiary carbon atoms, quaternary carbon atoms, or a combination thereof. Phrases containing this term, such as "C 1 ~C 3 "Alkyl" refers to an alkyl group containing 1 to 3 carbon atoms, each occurrence of which can be independently C 1 Alkyl, C 2 Alkyl or C 3Suitable examples include, but are not limited to, methyl (Me, -CH 3 ), ethyl (Et, -CH 2 CH 3 ), 1-propyl (n-propyl, n-Pr, n-propyl, -CH 2 CH 2 CH 3 ), 2-propyl (i-Pr, i-propyl, -CH (CH 3 ) 2 ).
[0072] In the present application, "alkoxy" refers to a group having an -O-alkyl group, i.e., an alkyl group as defined above connected to a parent core structure via an oxygen atom. Phrases containing this term, such as "C 1 ~C 3 "Alkoxy" means that the alkyl part contains 1 to 3 carbon atoms, each occurrence can be independently C 1 Alkoxy, C 2 Alkoxy or C 3 Suitable examples include, but are not limited to, methoxy (—O—CH 3 or -OMe), ethoxy (-O-CH 2 CH 3 or -OEt).
[0073] In the present application, "halogen" refers to F, Cl, Br or I.
[0074] At present, the adsorbents used for water purification mainly include activated carbon, natural modified materials, etc. Activated carbon is one of the most commonly used adsorbents. It has a highly developed pore structure and a huge specific surface area, which can effectively adsorb various organic and some inorganic substances. However, the lack of stability of activated carbon during the adsorption process will lead to poor adsorption performance and poor regeneration performance. Natural modified materials are obtained by modifying natural materials by physical or chemical methods. The methods for modifying natural materials mainly include acidification, alkalization, heat treatment and loading of metal ions. However, in the acidic or alkaline solution of the natural material loaded with metal ions, the metal ions may dissolve or fall off, resulting in a decrease in adsorption performance. At the same time, the above-mentioned modification methods such as acidification, alkalization, heat treatment and loading of metal ions also require precise control of reaction conditions, such as temperature, pressure, time, reagent concentration, etc. This increases the complexity and difficulty of the production process, which is not conducive to industrial application.
[0075] In addition, there are several methods for removing COD from water bodies: (1) Adding trisodium phosphate during wastewater treatment will cause precipitation reaction with calcium ions in the water, removing COD from the water while forming precipitation. However, this method is less effective in removing COD, with a removal rate of about 20-30%. (2) Using chitosan, which contains polyhydroxyl groups and has magnetism, as an adsorption material to absorb COD by magnetism. However, in solutions with low pH (pH ≤ 8.5), magnetic substances often lose their properties, which in turn affects the adsorption performance of chitosan, resulting in reduced adsorption performance.
[0076] Therefore, there is an urgent need to provide a method for preparing an adsorption material with a simple production process and excellent adsorption performance and regeneration performance.
[0077] Based on this, the first aspect of the present application provides a method for preparing a composite material, comprising the following steps:
[0078] S10: mixing monomers, initiators, crosslinking agents and pore-forming agents, and performing polymerization reaction to prepare a crosslinked polymer carrier;
[0079] S20: mixing the cross-linked polymer carrier and aminosulfonic acid in a solvent, and performing a substitution reaction to bond the aminosulfonic acid to the cross-linked polymer carrier, thereby preparing the composite material.
[0080] Wherein, the monomer includes one or more compounds having structural characteristics shown in formula (I) to formula (II):
[0081] , .
[0082] In formula (I), R 11 C 2 ~C 6 Alkynyl, substituted or unsubstituted C 2 ~C 6 Alkenyl; replace the C 2 ~C 6 Substituents for alkenyl groups include C 1 ~C 3 Alkyl and C 1 ~C 3 One or more of alkoxy groups.
[0083] In one example, in formula (I), R 11 -CH=CH 2 、-CH 2 CH=CH 2 、-CH 2 CH 2 CH 2 CH 2CH=CH 2 、-C≡CH、-CH 2 C≡CH, , or It can be understood that in this application, "*" represents a connection site.
[0084] R 11 The unsaturated hydrocarbon group can be chemically bonded with the cross-linking agent to form a stable cross-linked network structure. The cross-linked network structure can limit the movement of the polymer molecular chain, thereby improving the anti-interference ability of the cross-linked polymer carrier to changes in pH and temperature.
[0085] In one example, in formula (I), R 12 is a halogen. m1 and m2 are positive integers. 12 is a halogen, which can provide a reactive site for the bonding of aminosulfonic acid.
[0086] It is understood that the sum of m1 and m2 is ≤ the number of ring atoms. In one example, the sum of m1 and m2 is ≤ 4. For example, m1 is 1, 2, 3 or 4. m2 is 1, 2, 3 or 4.
[0087] In formula (II), the alkenyl group is located between the pyridazine ring and the benzene ring. The conjugated structure further increases the stability of the cross-linked polymer carrier and facilitates electron transfer, thereby increasing the adsorption of organic pollutants.
[0088] In one example, in formula (II), R 21 , R 22 and R 23 are each independently H or halogen, and R 21 , R 22 and R 23 At least one of them is halogen. n1 and n4 are each independently an integer from 1 to 5. n1 and n4 are each independently 1, 2, 3, 4 or 5.
[0089] In one example, in formula (II), n2 is 1 or 2.
[0090] In one example, in formula (II), n3 is any integer from 1 to 10. For example, n3 includes but is not limited to 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0091] In one example, in formula (II), R 21 , R 22 and R 23 Each is independently H, F or Cl.
[0092] In one example, the monomer includes 3-chloro-6-vinylpyridazine 、3,6-Chloro-4-vinylpyridazine , 3-chloro-6-(1-ethoxyvinyl)pyridazine and 2-(4-fluorobenzyl)-6-phenylvinylpyridazin-3(2H)-one One or more of .
[0093] The present application found that the monomer of the above structure can be efficiently cross-linked with a cross-linking agent to form a stable three-dimensional network structure. And the structure such as the pyridazine ring contained therein can adsorb organic pollutants in water such as phenol, p-hydroxybenzoic acid and oxalic acid through hydrogen bonding, π-π interactions, etc., thereby improving the adsorption performance. In addition, the halogen atoms contained in the monomer of the above structure can react with aminosulfonic acid, thereby achieving the bonding of aminosulfonic acid.
[0094] In one example, S20: mixing the cross-linked polymer carrier and aminosulfonic acid in a solvent, performing a substitution reaction, and bonding the aminosulfonic acid to the cross-linked polymer carrier. The steps of preparing the composite material include:
[0095] The cross-linked polymer carrier is swollen in a solvent, and the aminosulfonic acid is added and mixed to carry out a substitution reaction so that the aminosulfonic acid is bonded to the cross-linked polymer carrier to prepare the composite material.
[0096] The cross-linked polymer carrier is first subjected to a swelling treatment, which can expand the distance between polymer chain segments and expose internal active groups such as halogens to promote full contact and reaction with aminosulfonic acid. This provides more bonding sites for aminosulfonic acid, which is beneficial to increase the content of aminosulfonic acid in the composite material and ensure reaction efficiency and reaction uniformity.
[0097] In one example, the solvent includes one or more of N,N-dimethylformamide, ethanol, 1,4-dioxane and toluene.
[0098] In one example, the mass ratio of the cross-linked polymer carrier to the solvent is 1:(1~5). The present application limits the mass ratio of the cross-linked polymer carrier to the solvent, which can ensure that the system has suitable fluidity and dispersibility, and can avoid the system being too thin due to too much solvent, thereby affecting the effective reaction; and can prevent the cross-linked polymer carrier from being unable to swell sufficiently due to too little solvent, thereby affecting the bonding of aminosulfonic acid. For example, the mass ratio of the cross-linked polymer carrier to the solvent includes but is not limited to 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5 or 1:5, or within the range formed by any two of the above point values as endpoint values.
[0099] In one example, the mass ratio of the cross-linked polymer carrier to the aminosulfonic acid is 1:(0.1~0.6). The mass ratio of the cross-linked polymer carrier or the aminosulfonic acid is within this range, which can ensure that there is enough aminosulfonic acid to fully contact and react with the cross-linked polymer carrier, so that the carrier effectively bonds with the aminosulfonic acid; and can also avoid agglomeration caused by excessive aminosulfonic acid or unreacted aminosulfonic acid residue, which affects the purity and performance stability of the composite material. By way of example, the mass ratio of the cross-linked polymer carrier to the aminosulfonic acid includes but is not limited to 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55 or 1:0.6, or within the range formed by any two of the above point values as endpoint values.
[0100] In one example, the swelling process parameters include: swelling time is 2h~4h. For example, the swelling time includes but is not limited to 2h, 2.5h, 3h, 3.5h or 4h. It can be understood that in this application, the swelling time is room temperature. Further, the room temperature is 5℃~25℃.
[0101] In one example, the process parameters of the substitution reaction include: reaction temperature of 40°C to 70°C, and reaction time of 4h to 12h. Limiting the temperature and time of the substitution reaction can keep the molecular thermal motion relatively active, so as to provide sufficient energy for the reaction between the cross-linked polymer carrier and aminosulfonic acid and promote the reaction. At the same time, limiting the process parameters of the substitution reaction can also avoid problems such as increased side reactions caused by excessive temperature, decomposition of aminosulfonic acid or destruction of the carrier structure. For example, the reaction temperature includes but is not limited to 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, or any two of the above point values as the range of endpoint values. The reaction time includes but is not limited to 4h, 5h, 6h, 7h or 8h, or any two of the above point values as the range of endpoint values.
[0102] In one example, before performing S20: mixing the cross-linked polymer carrier and aminosulfonic acid in a solvent, performing a substitution reaction to bond the aminosulfonic acid to the cross-linked polymer carrier, the step of preparing the composite material further includes:
[0103] The cross-linked polymer support is subjected to a step of washing in a washing solvent.
[0104] Illustratively, the cleaning solvent includes one or more of methanol, ethanol, isopropanol, and isobutanol.
[0105] In one example, S10: mixing monomers, initiators, cross-linking agents, and pore-forming agents, and preparing a cross-linked polymer carrier by polymerization reaction includes:
[0106] S101: mixing the monomer, the cross-linking agent, the initiator and the pore-forming agent to prepare an oil phase solution;
[0107] S102: mixing a dispersant and a salting-out agent in a water solvent to prepare an aqueous phase solution;
[0108] S103: mixing the oil phase solution and the water phase solution, and performing a polymerization reaction to prepare the cross-linked polymer carrier.
[0109] It is understandable that the present application does not limit the order of step S101 and step S102. The oil phase solution may be prepared first, or the water phase solution may be prepared first.
[0110] The present application first prepares the oil phase solution and the aqueous phase solution separately, at which time the components can be fully mixed and uniform in their respective phases, which ensures the uniform dispersion of monomers, crosslinking agents, initiators and pore-forming agents in the oil phase solution, and dispersants and salting-out agents in the aqueous phase, thereby providing good starting conditions for subsequent polymerization reactions. In addition, after the oil phase and the aqueous phase are mixed, a polymerization reaction can be carried out, and a special reaction environment can be formed by means of the incompatibility of the two, which is conducive to controlling the rate and progress of the polymerization reaction. The salting-out agent can further adjust the phase separation behavior of the system to prepare a cross-linked polymer carrier with a suitable pore structure, which is convenient for the subsequent bonding of aminosulfonic acid.
[0111] The amount of initiator used plays an important role in ensuring the initiation of the monomer polymerization reaction and making the reaction proceed smoothly; and avoiding the problem of excessive initiator leading to increased side reactions or unstable polymer performance. In one example, the mass ratio of the monomer to the initiator is 1: (0.005~0.01). For example, the mass ratio of the monomer to the initiator includes but is not limited to 1: 0.005, 1: 0.006, 1: 0.007, 1: 0.008, 1: 0.009 or 1: 0.01, or any two of the above point values as the range of endpoint values.
[0112] The content of the cross-linking agent plays an important role in ensuring sufficient cross-linking with the monomer to form a stable three-dimensional network structure. In one example, the mass ratio of the monomer to the cross-linking agent is 1: (0.03~0.1). For example, the mass ratio of the monomer to the cross-linking agent includes but is not limited to 1: 0.03, 1: 0.04, 1: 0.05, 1: 0.06, 1: 0.07, 1: 0.08, 1: 0.09 or 1: 0.1, or within the range formed by any two of the above point values as endpoint values.
[0113] In one example, the mass ratio of the monomer to the pore-forming agent is 1:(0.3~5). This mass ratio allows the pore-forming agent to function effectively to form a rich and suitable pore structure in the cross-linked polymer carrier, thereby improving its specific surface area and adsorption performance. For example, the mass ratio of the monomer to the pore-forming agent includes but is not limited to 1:0.3, 1:0.35, 1:0.4, 1:0.45 or 1:0.5, or within the range formed by any two of the above point values as endpoint values.
[0114] In one example, the initiator includes one or more of benzoyl peroxide, azobisisobutyronitrile, cumene hydroperoxide and tert-butyl hydroperoxide.
[0115] In one example, the cross-linking agent includes one or more of divinylbenzene, ethylene glycol dimethacrylate, allyl methacrylate, allyl itaconate, and allyl isocyanurate.
[0116] It can be understood that in the present application, the cross-linked polymer carrier prepared is a polymer of a cross-linking agent and a monomer. For example, when the cross-linking agent is divinylbenzene and the monomer is 3-chloro-6-vinylpyridazine, the cross-linked polymer carrier is . m and n are positive integers.
[0117] At this time, the reaction that occurs corresponds to .
[0118] In one example, the pore former includes one or more of cyclohexane, ethylene dichloride, benzene, toluene and xylene.
[0119] To make the dispersant fully dispersed in the water solvent. In one example, the mass ratio of the dispersant to the water solvent is 1: (80-200). For example, the mass ratio of the dispersant to the water solvent includes but is not limited to 1: 80, 1: 85, 1: 90, 1: 95, 1: 98, 1: 100, 1: 102, 1: 105, 1: 120, 1: 140, 1: 160, 1: 180 or 1: 200, or any two of the above point values as endpoint values.
[0120] In one example, the mass ratio of the dispersant to the salting-out agent is 1:(30-60). For example, the mass ratio of the dispersant to the salting-out agent includes but is not limited to 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:58 or 1:60, or a range formed by any two of the above point values as endpoint values.
[0121] In one example, the dispersing agent includes one or more of polyethylene glycol and gelatin.
[0122] In one example, the salting-out agent includes one or more of magnesium sulfate, sodium carbonate, sodium chloride, calcium chloride and ammonium chloride.
[0123] In one example, the mass ratio of the oil phase solution and the aqueous phase solution is 1:(1~8). Limiting the mass ratio of the oil phase solution and the aqueous phase solution to this range can ensure that a suitable reaction system environment is formed during mixing, which can avoid the slow polymerization rate or difficulty in forming an ideal cross-linked polymer carrier structure caused by too much water phase, and can avoid problems such as system instability and uneven mixing caused by too high an oil phase ratio. Through the precise control of this ratio, the smooth progress of the polymerization reaction can be effectively promoted. For example, the mass ratio of the oil phase solution and the aqueous phase solution includes but is not limited to 1:1, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:3, 1:4, 1:5, 1:6, 1:7 or 1:8, or within the range formed by any two of the above point values as endpoint values.
[0124] In one example, the polymerization reaction includes a first polymerization reaction and a second polymerization reaction performed sequentially.
[0125] In one example, the process parameters of the first polymerization reaction include: a polymerization temperature of 60°C to 80°C, and a polymerization time of 2h to 5h. For example, the polymerization temperature of the first polymerization reaction includes but is not limited to 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 74°C, 75°C, 76°C, 78°C or 80°C. The time of the first polymerization reaction includes but is not limited to 2h, 2.5h, 2.8h, 2.9h, 3h, 3.2h, 3.5h, 4h, 4.5h or 5h.
[0126] In one example, the process parameters of the second polymerization reaction include: a polymerization temperature of 95°C to 120°C, and a polymerization time of 10h to 18h. For example, the polymerization temperature of the second polymerization reaction includes but is not limited to 95°C, 98°C, 100°C, 101°C, 103°C, 105°C, 107°C, 110°C, 115°C or 120°C. The time of the second polymerization reaction includes but is not limited to 10h, 11h, 12h, 14h, 16h or 18h.
[0127] The present application has found that carrying out the first polymerization reaction and the second polymerization reaction at different temperatures is more conducive to forming a cross-linked polymer, thereby further improving the adsorption and regeneration capabilities of the composite material for organic pollutants.
[0128] In one example, before the step of performing the polymerization reaction, the step further includes:
[0129] The step of stabilizing the mixed oil phase solution and the aqueous phase solution. For example, the process parameters for stabilizing the mixed oil phase solution and the aqueous phase solution include: a rotation speed of 50 rpm to 200 rpm. For example, the rotation speed for stabilizing the mixed solution of the oil phase solution and the aqueous phase solution includes but is not limited to 50 rpm, 80 rpm, 100 rpm, 120 rpm, 140 rpm, 160 rpm, 180 rpm or 200 rpm, or within the range formed by any two of the above point values as endpoint values.
[0130] In this application, "aminosulfonic acid" refers to .
[0131] A second aspect of the present application provides a composite material prepared by the preparation method described in any example of the first aspect of the present application.
[0132] The composite material comprises: a cross-linked polymer carrier and aminosulfonic acid bonded to the cross-linked polymer carrier.
[0133] The cross-linked polymer carrier is obtained by polymerization reaction of the monomer, the initiator, the cross-linking agent and the pore-forming agent.
[0134] Wherein, the mass ratio of the cross-linked polymer carrier to the aminosulfonic acid is 1:(0.1-0.6). For example, the mass ratio of the cross-linked polymer carrier to the aminosulfonic acid includes but is not limited to 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45 or 1:0.5, or a range formed by any two of the above point values as endpoint values.
[0135] The third aspect of the present application provides a wastewater purification method, comprising the following steps: using the composite material described in the second aspect of the present application to perform adsorption treatment on a water body.
[0136] In one example, the wastewater includes one or more of phenol, p-hydroxybenzoic acid and oxalic acid.
[0137] Phenol, p-hydroxybenzoic acid and oxalic acid are the main sources of chemical oxygen demand in wastewater. The above substances are all organic matter and have certain reducing properties. In the wastewater environment, the above organic pollutants can react chemically with strong oxidants, thereby consuming a large amount of oxidants and causing the chemical oxygen demand value to increase.
[0138] In one example, the process parameters of the adsorption treatment include: the flow rate of the wastewater is 1BV / h~3BV / h. Within this flow rate range, the wastewater and the composite material can have sufficient contact time, so that the adsorption sites in the composite material can effectively capture organic pollutants such as phenol, p-hydroxybenzoic acid and oxalic acid in the wastewater, thereby improving the adsorption efficiency and ensuring a good purification effect. By way of example, the flow rate of the wastewater includes but is not limited to 1BV / h, 1.5 BV / h, 2 BV / h, 2.5BV / h or 3 BV / h, or within the range formed by any two of the above point values as endpoint values.
[0139] The following further specific examples are used to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by technicians in this field based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters and the like in the following examples are also only an example within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description of this article, and are not necessarily limited to the specific values in the examples below.
[0140] Example 1
[0141] Embodiment 1 of the present application provides a composite material and a preparation method thereof, comprising the following steps:
[0142] (1) Preparation of oil phase solution: 3-chloro-6-vinylpyridazine (monomer), divinylbenzene (cross-linking agent), benzoyl peroxide (initiator) and toluene (pore-forming agent) were mixed in a mass ratio of 1:0.05:0.01:0.3 to prepare an oil phase solution.
[0143] (2) Preparation of aqueous solution: gelatin (dispersant), sodium chloride (salting-out agent) and water solvent are mixed in a mass ratio of 1:60:100 to prepare an aqueous solution.
[0144] (3) Preparation of a cross-linked polymer carrier: The aqueous solution was added to a flask, and then the oil phase solution was added. The mass ratio of the oil phase solution to the aqueous solution was 1:2. The rotation speed was adjusted to 100 rpm to stabilize the mixture of the aqueous solution and the oil phase solution. The temperature was then raised to 75°C and kept for 3 h to carry out a first polymerization reaction. The temperature was then raised to 101°C and kept for 12 h to carry out a second polymerization reaction to prepare the cross-linked polymer carrier.
[0145] (4) Washing: Wash the cross-linked polymer carrier in ethanol for 2 h to 8 h.
[0146] (5) Preparation of composite materials: The washed cross-linked polymer carrier was swollen in N, N-dimethylformamide (solvent) for 2 hours, wherein the mass ratio of the cross-linked polymer carrier to N, N-dimethylformamide was 1:5; then aminosulfonic acid was added (the mass ratio of the cross-linked polymer carrier to aminosulfonic acid was 1:0.3), and the temperature was raised to 70°C for 8 hours for substitution reaction to bond the aminosulfonic acid to the cross-linked polymer carrier to prepare a composite material. The composite material was washed with ethanol and water. The particle size of the prepared composite material was tested to be 0.3 mm to 1.0 mm, and the particle strength was >4N.
[0147] In the preparation process of the composite material of Example 1, the chemical reactions involved are mainly as follows:
[0148] .
[0149] Example 2
[0150] Embodiment 2 of the present application provides a composite material and a preparation method thereof, comprising the following steps:
[0151] (1) Preparation of oil phase solution: 3,6-chloro-4-vinylpyridazine (monomer), divinylbenzene (cross-linking agent), benzoyl peroxide (initiator) and toluene (pore-forming agent) were mixed in a mass ratio of 1:0.05:0.01:0.3 to prepare an oil phase solution.
[0152] (2) Preparation of aqueous solution: gelatin (dispersant), sodium chloride (salting-out agent) and water solvent are mixed in a mass ratio of 1:60:100 to prepare an aqueous solution.
[0153] (3) Preparation of a cross-linked polymer carrier: The aqueous solution was added to a flask, and then the oil phase solution was added. The mass ratio of the oil phase solution to the aqueous solution was 1:2. The rotation speed was adjusted to 100 rpm to stabilize the mixture of the aqueous solution and the oil phase solution. The temperature was then raised to 75°C and kept for 3 h to carry out a first polymerization reaction. The temperature was then raised to 101°C and kept for 12 h to carry out a second polymerization reaction to prepare the cross-linked polymer carrier.
[0154] (4) Washing: Wash the cross-linked polymer carrier in ethanol for 2 h to 8 h.
[0155] (5) Preparation of composite materials: The washed cross-linked polymer carrier was swollen in N, N-dimethylformamide (solvent) for 2 h, wherein the mass ratio of the cross-linked polymer carrier to N, N-dimethylformamide was 1:5; then aminosulfonic acid was added (the mass ratio of the cross-linked polymer carrier to aminosulfonic acid was 1:0.3), and the temperature was raised to 70°C for 8 h for substitution reaction to bond the aminosulfonic acid to the cross-linked polymer carrier to prepare a composite material. The composite material was washed with ethanol and water. The particle size of the prepared composite material was tested to be 0.3 mm ~1.0 mm, and the particle strength was >4N.
[0156] In the preparation process of the composite material of Example 2, the chemical reactions involved are mainly as follows:
[0157] .
[0158] Example 3
[0159] Embodiment 3 of the present application provides a composite material and a preparation method thereof, comprising the following steps:
[0160] (1) Preparation of oil phase solution: 3-chloro-6-(1-ethoxyvinyl)pyridazine (monomer), divinylbenzene (cross-linking agent), benzoyl peroxide (initiator) and toluene (pore-forming agent) were mixed in a mass ratio of 1:0.05:0.01:0.3 to prepare an oil phase solution.
[0161] (2) Preparation of aqueous solution: gelatin (dispersant), sodium chloride (salting-out agent) and water solvent are mixed in a mass ratio of 1:60:100 to prepare an aqueous solution.
[0162] (3) Preparation of a cross-linked polymer carrier: The aqueous solution was added to a flask, and then the oil phase solution was added. The mass ratio of the oil phase solution to the aqueous solution was 1:2. The rotation speed was adjusted to 100 rpm to stabilize the mixture of the aqueous solution and the oil phase solution. The temperature was then raised to 75°C and kept for 3 h to carry out a first polymerization reaction. The temperature was then raised to 101°C and kept for 12 h to carry out a second polymerization reaction to prepare the cross-linked polymer carrier.
[0163] (4) Washing: Wash the cross-linked polymer carrier in ethanol for 2 h to 8 h.
[0164] (5) Preparation of composite materials: The washed cross-linked polymer carrier was swollen in N, N-dimethylformamide (solvent) for 2 hours, wherein the mass ratio of the cross-linked polymer carrier to N, N-dimethylformamide was 1:5; then aminosulfonic acid was added (the mass ratio of the cross-linked polymer carrier to aminosulfonic acid was 1:0.3), and the temperature was raised to 70°C for 8 hours for substitution reaction to bond the aminosulfonic acid to the cross-linked polymer carrier to prepare a composite material. The composite material was washed with ethanol and water. The particle size of the prepared composite material was tested to be 0.5 mm to 1.2 mm, and the particle strength was >3N.
[0165] In the preparation process of the composite material of Example 3, the chemical reactions involved are mainly as follows:
[0166] .
[0167] Example 4
[0168] Example 4 is basically the same as Example 1, with the main difference being that in step (5) of Example 4, the mass ratio of the cross-linked polymer carrier to aminosulfonic acid is 1:0.1. The particle size of the prepared composite material is 0.3 mm to 1.0 mm, and the particle strength is >4N.
[0169] Example 5
[0170] Example 5 is basically the same as Example 1, with the main difference being that in step (5) of Example 5, the mass ratio of the cross-linked polymer carrier to aminosulfonic acid is 1:0.6. The particle size of the prepared composite material is 0.3 mm to 1.0 mm, and the particle strength is >4N.
[0171] Example 6
[0172] Example 6 is basically the same as Example 1, with the main difference being that the specific steps of step (3) of Example 6 include:
[0173] (3) Preparation of cross-linked polymer carrier: The aqueous phase solution was added to a flask, and then the oil phase solution was added. The mass ratio of the oil phase solution to the aqueous phase solution was 1:2. The rotation speed was adjusted to 100 rpm to stabilize the mixture of the aqueous phase solution and the oil phase solution. The temperature was then raised to 101°C and kept for 12 hours to perform a polymerization reaction to prepare the cross-linked polymer carrier. The particle size of the prepared composite material was tested to be 0.3~1.0 mm, and the particle strength was >4N.
[0174] Example 7
[0175] Example 7 is basically the same as Example 1, the main difference being that the crosslinking agent selected in step (1) of Example 7 is allyl itaconate. The particle size of the prepared composite material is 0.3 mm to 1.0 mm, and the particle strength is >5N.
[0176] Comparative Example 1
[0177] Comparative Example 1 is substantially the same as Example 1, except that the step of adding aminosulfonic acid is not included in Comparative Example 1. Specifically, step (5) of Comparative Example 1 includes:
[0178] (5) Preparation of composite materials: The washed cross-linked polymer carrier was swollen in N, N-dimethylformamide (solvent) for 2 h, wherein the mass ratio of the cross-linked polymer carrier to N, N-dimethylformamide was 1:5; then the temperature was raised to 70°C for 8 h to prepare a composite material. The composite material was washed with ethanol and water.
[0179] Comparative Example 2
[0180] Comparative Example 2 is substantially the same as Example 1, with the main difference being that Comparative Example 2 does not include step (5).
[0181] Comparative Example 3
[0182] Comparative Example 3 is substantially the same as Example 1, the main difference being that the monomer used in step (1) of Comparative Example 3 is propyl methacrylate.
[0183] Comparative Example 4
[0184] Comparative Example 4 is substantially the same as Example 1, except that benzenesulfonic acid is used in step (5) of Comparative Example 4. Step (5) specifically comprises:
[0185] Preparation of composite materials: The washed cross-linked polymer carrier was swollen in N, N-dimethylformamide (solvent) for 2 hours, wherein the mass ratio of the cross-linked polymer carrier to N, N-dimethylformamide was 1:5; then benzenesulfonic acid was added (the mass ratio of the cross-linked polymer carrier to benzenesulfonic acid was 1:0.3), and the temperature was raised to 70°C for 8 hours to react to prepare the composite material. The composite material was washed with ethanol and water.
[0186] Figure 1 This is the FTIR spectrum of the composite material prepared in Example 1 of the present application. Figure 1 Visible, 1654cm -1 There is an obvious peak at 1048cm, indicating the presence of a CN bond. Pyridazine is indeed present in the polymerized monomer. -1 and 1100cm -1 This indicates the presence of obvious sulfonic acid groups in the material, indicating the successful use of aminosulfonic acid to obtain the target structure.
[0187] The composite materials prepared in the above embodiments and comparative examples were used as adsorbents to adsorb wastewater. The specific steps include: taking 10 mL of the composite materials prepared in the above embodiments and comparative examples, respectively, filling the composite materials into a glass chromatography column, treating 10 BV of wastewater (the wastewater is laboratory-made wastewater, pH 8, and the wastewater contains: 1346 ppm of phenol, 874 ppm of p-hydroxybenzoic acid, and 46 ppm of oxalic acid), with a flow rate of 1 BV / h. The contents of phenol, p-hydroxybenzoic acid, and oxalic acid in the water discharged after treatment with the above composite materials were determined using high performance liquid chromatography, and the results are shown in Table 1.
[0188] Table 1 Adsorption effect of composite materials on organic pollutants
[0189]
[0190] As can be seen from Table 1, Examples 1 to 3 of the present application are basically the same, and the main difference is that different monomer types are selected. Among them, Example 1 selects 3-chloro-6-vinylpyridazine, and the composite material prepared in this case has better adsorption performance for organic pollutants.
[0191] Using 10% NaOH solution as a regeneration agent, the composite material after the first adsorption treatment in the above-mentioned embodiment and comparative example is desorbed and regenerated, and the phenol, p-hydroxybenzoic acid and oxalic acid contents in the first effluent are recorded. Then the composite material after regeneration is adsorbed on the above-mentioned wastewater for a second adsorption treatment, and after desorption and regeneration under the same conditions, the phenol, p-hydroxybenzoic acid and oxalic acid contents of the second effluent are recorded. The composite material after the second regeneration is adsorbed on the above-mentioned wastewater for a third adsorption treatment, and then desorption and regeneration under the same conditions are recorded. The phenol, p-hydroxybenzoic acid and oxalic acid contents of the third effluent are recorded. The average regeneration rate of the composite material of the embodiment and comparative example is calculated based on the phenol, p-hydroxybenzoic acid and oxalic acid contents in the first effluent, the phenol, p-hydroxybenzoic acid and oxalic acid contents in the second effluent, and the phenol, p-hydroxybenzoic acid and oxalic acid contents in the third effluent. The corresponding average regeneration rate is calculated as follows: [(phenol, p-hydroxybenzoic acid and oxalic acid content in the first effluent / phenol, p-hydroxybenzoic acid and oxalic acid content adsorbed in the first adsorption treatment) + (phenol, p-hydroxybenzoic acid and oxalic acid content in the second effluent / phenol, p-hydroxybenzoic acid and oxalic acid content adsorbed in the second adsorption treatment) + (phenol, p-hydroxybenzoic acid and oxalic acid content in the third effluent / phenol, p-hydroxybenzoic acid and oxalic acid content adsorbed in the third adsorption treatment)] / 3. The average regeneration rate data of the composite material obtained after repeating 3 times are shown in Table 2.
[0192] Table 2 Comparison of average regeneration rates of composite materials
[0193]
[0194] As can be seen from Table 1 to Table 2, no aminosulfonic acid is added to Comparative Example 1, and the composite material prepared at this time has poor adsorption capacity for organic pollutants such as phenol, and its regeneration performance is poor, so it cannot meet actual needs. Comparative Example 2 only uses the prepared cross-linked polymer carrier to adsorb wastewater, and it also shows poor adsorption performance and regeneration performance. The monomer selected in Comparative Example 3 is propyl methacrylate, and the composite material prepared at this time has weak adsorption capacity for organic pollutants and regeneration capacity after adsorption. Comparative Example 4 uses benzenesulfonic acid, and similar to Comparative Example 3, the composite material of Comparative Example 4 has weak adsorption capacity for organic pollutants and regeneration capacity after adsorption. This shows that the composite material prepared by using pyridazine monomers and aminosulfonic acid in this application has excellent adsorption performance and regeneration capacity in wastewater purification.
[0195] Examples 1 to 3 of the present application are basically the same, the main difference being that different monomer types are selected. As can be seen from Tables 1 and 2, Example 1 selects 3-chloro-6-vinylpyridazine, and the composite material prepared at this time has a better adsorption effect on organic pollutants such as phenol, and has a more excellent regeneration ability.
[0196] Embodiment 1, embodiment 4 and embodiment 5 are basically the same, and the main difference is that the mass ratio of the cross-linked polymer carrier and aminosulfonic acid is different. The composite material in embodiment 4 has certain adsorption performance and relatively excellent regeneration performance for organic pollutants. As the content of aminosulfonic acid increases, the adsorption capacity of the composite material for organic pollutants in wastewater is enhanced, but in embodiment 5, it is also accompanied by the weakening of regeneration capacity. This shows that the mass ratio of the cross-linked polymer carrier and aminosulfonic acid plays an important role in the performance of the composite material.
[0197] In Example 6, the cross-linked polymer carrier is prepared by a single polymerization reaction. The composite material prepared at this time has good organic pollutant adsorption capacity and regeneration performance, but its technical effect is slightly worse than that of Example 1 in which the composite material is prepared by a secondary polymerization reaction.
[0198] The main difference between Example 7 and Example 1 is that different types of crosslinking agents are used, resulting in different crosslinked polymer carriers. From the technical effect point of view, the composite material including 3-chloro-6-vinylpyridazine and divinylbenzene crosslinked structure in Example 1 exhibits better adsorption performance and regeneration performance.
[0199] The technical features of the above examples can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0200] The examples described above only express several implementation methods of the present application, which are convenient for understanding the technical solutions of the present application in a specific and detailed manner, but they cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present application, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description can be used to interpret the contents of the claims.
Claims
1. A method for preparing a composite material, characterized in that: The following steps are involved: Mixing monomers, initiators, crosslinking agents and pore-forming agents, and performing polymerization reaction to prepare a crosslinked polymer carrier; The cross-linked polymer carrier and aminosulfonic acid are mixed in a solvent, and a substitution reaction is performed to bond the aminosulfonic acid to the cross-linked polymer carrier to prepare the composite material; Wherein, the monomer includes one or more compounds having structural characteristics shown in formula (I) to formula (II): 、 ; R 11 is C2~C6 alkynyl, substituted or unsubstituted C2~C6 alkenyl; the substituents replacing the C2~C6 alkenyl include one or more of C1~C3 alkyl and C1~C3 alkoxy; R 12 is a halogen; m1 and m2 are positive integers, and the sum of m1 and m2 is ≤4; R 21 , R 22 and R 23 are each independently H or halogen, and R 21 , R 22 and R 23 At least one of them is a halogen; n1 and n4 are each independently an integer from 1 to 5, n2 is 1 or 2, and n3 is an integer from 1 to 10.
2. The method for preparing a composite material according to claim 1, characterized in that: The monomer has one or more of the following characteristics: (1) In formula (I), R 11 For -CH=CH2, -CH2CH=CH2, -CH2CH2CH2CH2CH=CH2, -C≡CH, -CH2C≡CH, , or ; (2) In formula (II), R 21 , R 22 and R 23 Each is independently H, F or Cl.
3. The method for preparing a composite material according to claim 1, characterized in that: The monomers include , , and One or more of .
4. The preparation method according to any one of claims 1 to 3, characterized in that The cross-linked polymer carrier and aminosulfonic acid are mixed in a solvent, and a substitution reaction is performed to bond the aminosulfonic acid to the cross-linked polymer carrier. The steps of preparing the composite material include: The cross-linked polymer carrier is swollen in a solvent, and the aminosulfonic acid is added and mixed to carry out a substitution reaction so that the aminosulfonic acid is bonded to the cross-linked polymer carrier to prepare the composite material.
5. The preparation method according to claim 4, characterized in that: The steps of preparing the composite material have one or more of the following characteristics: (1) The solvent includes one or more of N,N-dimethylformamide, ethanol, 1,4-dioxane and toluene; (2) The mass ratio of the cross-linked polymer carrier to the solvent is 1:(1-5); (3) The mass ratio of the cross-linked polymer carrier to the aminosulfonic acid is 1:(0.1-0.6); (4) The swelling process parameters include: swelling temperature is room temperature, swelling time is 2h~4h; (5) The process parameters of the substitution reaction include: reaction temperature of 40°C to 70°C, and reaction time of 4h to 12h.
6. The preparation method according to any one of claims 1 to 3, characterized in that The steps of mixing monomers, initiators, crosslinking agents and pore-forming agents to prepare a crosslinked polymer carrier through polymerization reaction include: Mixing the monomer, the cross-linking agent, the initiator and the pore-forming agent to prepare an oil phase solution; Mixing a dispersant and a salting-out agent in a water solvent to prepare an aqueous phase solution; The oil phase solution and the water phase solution are mixed and subjected to polymerization reaction to prepare the cross-linked polymer carrier.
7. The preparation method according to claim 6, characterized in that: The step of preparing the cross-linked polymer carrier has one or more of the following characteristics; (1) The mass ratio of the monomer to the initiator is 1:(0.005-0.01); (2) The mass ratio of the monomer to the cross-linking agent is 1:(0.03-0.1); (3) The mass ratio of the monomer to the pore-forming agent is 1:(0.3-5); (4) The initiator includes one or more of benzoyl peroxide, azobisisobutyronitrile, cumene hydroperoxide and tert-butyl hydroperoxide; (5) The crosslinking agent includes one or more of divinylbenzene, ethylene glycol dimethacrylate, allyl methacrylate, allyl itaconate and allyl isocyanurate; (6) The pore-forming agent includes one or more of cyclohexane, ethylene dichloride, benzene, toluene and xylene; (7) The mass ratio of the dispersant to the aqueous solvent is 1:(80-200); (8) The mass ratio of the dispersant to the salting-out agent is 1:(30-60); (9) The dispersant includes one or more of polyethylene glycol and gelatin; (10) The salting-out agent includes one or more of magnesium sulfate, sodium carbonate, sodium chloride, calcium chloride and ammonium chloride; (11) The mass ratio of the oil phase solution to the water phase solution is 1:(1-8).
8. The preparation method according to claim 6, characterized in that: The polymerization reaction includes a first polymerization reaction and a second polymerization reaction performed sequentially; The process parameters of the first polymerization reaction include: polymerization temperature of 60°C to 80°C, polymerization time of 2h to 5h; The process parameters of the second polymerization reaction include: polymerization temperature of 95° C. to 120° C., and polymerization time of 10 h to 18 h.
9. A composite material, characterized in that: The composite material is prepared by the preparation method according to any one of claims 1 to 8; the composite material comprises: a cross-linked polymer carrier and aminosulfonic acid bonded to the cross-linked polymer carrier; wherein the cross-linked polymer carrier is obtained by polymerization reaction of the monomer, the initiator, the cross-linking agent and the pore-forming agent; The composite material has one or more of the following characteristics: (1) The particle size of the composite material is 0.3 mm to 1.2 mm; (2) The particle strength of the composite material is greater than 3N.
10. A method for purifying wastewater, characterized in that: The method comprises the following steps: using the composite material according to claim 9 to perform adsorption treatment on a water body; the wastewater purification method has one or more of the following characteristics: (1) The wastewater contains one or more of phenol, p-hydroxybenzoic acid and oxalic acid; (2) The process parameters of the adsorption treatment include: the flow rate of the wastewater is 1BV / h~3BV / h.
Citation Information
Cited By
Bilirubin adsorbent as well as preparation method and application thereof
CN121130851A